2000
DOI: 10.1177/002215540004801212
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Renin–Angiotensin System (RAS) Components by Normal and Tumoral Lactotropes: A Comparative Study Using Reverse Hemolytic Plaque Assay (RHPA) and Immunoelectron Microscopy

Abstract: S U M M A R YImmunodetection of renin-angiotensin system (RAS) components indicates that there is a local RAS in anterior pituitary cells, particularly in lactotropes. We have attempted to determine if RAS molecules are secreted by lactotropes and the secretory pathways and intracellular sites of maturation. We investigated the secretory activity of individual lactotropes, using the reverse hemolytic plaque assay (RHPA), with GH3B6 tumor cells and normal male rat pituitary cells. We also determined the subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The appearance of a sophisticated kidney function in mammals made it possible the efficient regulation of blood volume and blood pressure through the activation of the systemic renin angiotensin aldosterone system (RAAS). Independently of a circulatory RAAS, the expression of RAAS components at cellular level in vertebrates because immunodetection of renin-angiotensin system (RAS) components were found in anterior pituitary cells, particularly in lactotropes [36] and prorenin, renin and angiotensinogen were identified not only in lactotropes and gonadotropes but also in somatotropes, corticotropes, and thyrotropes. The highest levels of renin were detected in lactotropes and gonadotropes [37].…”
Section: Components Of Raas Are Involved In Cell Volume Regulation Inmentioning
confidence: 99%
“…The appearance of a sophisticated kidney function in mammals made it possible the efficient regulation of blood volume and blood pressure through the activation of the systemic renin angiotensin aldosterone system (RAAS). Independently of a circulatory RAAS, the expression of RAAS components at cellular level in vertebrates because immunodetection of renin-angiotensin system (RAS) components were found in anterior pituitary cells, particularly in lactotropes [36] and prorenin, renin and angiotensinogen were identified not only in lactotropes and gonadotropes but also in somatotropes, corticotropes, and thyrotropes. The highest levels of renin were detected in lactotropes and gonadotropes [37].…”
Section: Components Of Raas Are Involved In Cell Volume Regulation Inmentioning
confidence: 99%
“…Immunohistochemical studies have demonstrated that anterior pituitary cells are also able to express the components of RAS [34, 35]. At the other hand, angiotensin peptides have been shown to affect the growth of anterior pituitary cells.…”
Section: Discussionmentioning
confidence: 99%